First‐in‐human [18F]D2‐Deprenyl‐PET imaging and GFAP evaluation as biomarkers of reactive astrogliosis in neurodegenerative diseases. (20th December 2022) - Katzdobler, Sabrina; Vogler, Letizia; Eckenweber, Florian; Nübling, Georg; Palleis, Carla; Lindner, Simon; Fietzek, Urban; Nuscher, Brigitte; Mueller, Andre; Koglin, Norman; Stephens, Andrew W; Haass, Christian; et al.
Abstract: Background: Neuroinflammation is a process occurring in neurodegenerative diseases, such as Alzheimer's Disease (AD) and parkinsonian syndromes. In light of emerging disease modifying trials, objective biomarkers are urgently needed. Here, we target reactive astrogliosis for biomarker development in a pilot cohort of Multiple System Atrophy (MSA), in which key pathology and associated neuroinflammation are regionally more restricted than in AD, but more pronounced than in Parkinson's Disease (PD). We combine glial fibrillary acidic protein (GFAP) as fluid‐based biomarker with [ 18 F]D2‐Deprenyl‐(DED)‐PET imaging, a novel PET tracer targeting MAO‐B, for comprehensive characterization of reactive astrogliosis in this model disease. Method: GFAP levels were analyzed in plasma samples of 23 MSA and 22 PD patients, as well as in CSF samples of 14 MSA and 14 PD patients. In a subset of patients (4 MSA‐P, 7 MSA‐C and 3 PD), first‐in‐human [ 18 F]DED‐PET imaging was performed. Fluid‐based and PET‐imaging biomarker levels were cross‐sectionally compared, followed by correlation to clinical disease severity as indicated by UMSARS (Unified Multiple System Atrophy Rating Scale) and MDS‐UPDRS (MDS Unified Parkinson's Disease Rating Scale). Correlation between fluid‐based biomarkers and PET imaging signals was performed. Two additional patients were on rasagiline treatment and proved target engagement of [ 18 F]DED‐PET imaging. Result: [ 18 F]DED‐PET imaging showed significantly higher SUVr signals in various regions of MSA when compared to PD. Signal increases were seen in phenotype‐specific target regions with higher putaminal tracer binding in MSA‐P and higher cerebellar tracer binding in MSA‐C patients (Fig. 1). Decreased [ 18 F]DED‐PET tracer signal was detected in patients on rasagiline treatment, indicating sufficient blocking (Fig. 2). While CSF and plasma GFAP levels did not differ between MSA and PD, GFAP levels in both biofluids correlated with disease severity in MSA (p < 0.05), but not in PD. Conclusion: We present first‐in‐human data on a novel PET tracer to detect reactive astrogliosis in MSA. While [ 18 F]DED‐PET imaging identifies disease‐ and entity‐specific regional astrogliosis, fluid biomarkers representing the overall level of astrogliosis appear to reflect clinical disease burden. Translation of these biomarkers into other neurodegenerative diseases, such as AD, should be pursued.